Batch and continuous flow mechanochemical synthesis of organic compounds including APIs - Atapalkar, Ranjit S.; Kulkarni, Amol A. (Reaction Chemistry and Engineering, 2023)
Mechanochemistry is becoming an enabling technology for the synthesis of organic and inorganic compounds as well as for the synthesis of polymers as it underlines sustainability in a significant manner. Continuous mechanochemical synthesis further adds value to the approach through consistency, smaller footprint, and better energy efficiency. This review gives an indepth view of the present status of this subject along with critical engineering aspects that one needs to measure and monitor as eventually synthesis needs to be transformed into a process. The examples covered herein include the synthesis of organic compounds, viz., APIs, agrochemical intermediates, catalysts, and polymers. In the end, we also discuss the safety aspects of mechanochemical synthesis and recommendations for exploring this field further. Mechanochemistry is becoming an enabling technology for the synthesis of organic and inorganic compounds as well as for the synthesis of polymers as it underlines sustainability in a significant manner.
Keywords: acids; Amides; Force; solvent